The “Painted Portal” of the cathedral of Lausanne: Tentative of interpretation of a singular sculptural program - Jalla, Marco (Eikón / Imago, 2012)
In the Middle Ages, crowds of pilgrims went to Lausanne to venerate the miraculous statue of Our Lady. They entered the building through the portal built around 1230 against the southern facade. Called "painted Portal" because of the rich polychromy adorning all the sculptures, it presents an amazing iconography of the Coronation of the Virgin. We believe that a careful reading of the eight Homilies of St. Amadeus, monk-bishop of Lausanne (✝ 1159), can explain the uniqueness of the imaging. By seeking to understand the meaning of the iconographic differences of the painted Portal, we describe how the image exalts the remarkable Marian devotion peculiar to the cathedral of Lausanne.